Quality Function Deployment Sebagai Upaya Peningkatan Kualitas Pelayanan PT KAI Di Era Pandemi Covid19 - Handy Nur Cahya; Windasari Windasari (Jurnal Dinamika Ekonomi & Bisnis, 2021)
Implementing health protocols during the COVID-19 pandemic is one of the company's efforts to provide services to customers. One of the evaluation services to adapt to customer preferences changes are applying a Quality Function Deployment (QFD). QFD is a method used to know customer needs and formulate how the company determines the priorities for meeting these needs based on company conditions.  Based on this research in Madiun Railway Station, the Quality Function Deployment shows three service attributes are getting on the top priority of customer needs. These are the implementation of health protocols, physical distancing, and hospitality of employees. The three service attributes will be developed and improved based on three out of the sixteen technical responses. These Technical Responses are improving the service and performance of employees, complete the information on social media, and make sure the environment and the toilet are clean.